STUDENTS’ PREFERENCES TOWARD LECTURERS’ TYPES IN GIVING CORRECTIVE FEEDBACK ON THEIR SPEAKING - Silfia Rahmi; Sirajul Munir (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
The current study aims at investigating the students’ preferences toward types of corrective feedback applied by the lecturers on their speaking. This research used a descriptive method. The participants of this research were 151 non English department students who took English subject. The instruments used to collect the data were questionnaire and interview guide. Those were adapted from Hyang (2010), Katayama (2007), together with Smith. They became the guideline on this research. The data gathered from questionaire were analyzed by using formula suggested by Heaton and Arikunto. Then, the data obtained from interview guide were analyzed by using theory proposed by Miles and Huberman. The research findings indicate that most students preferred to receive explicit corrective feedback using metalinguistic correction. It was caused by lack of language exposure due to limited language knowledge they possess.